Simulação da intensidade de infestação de Diatraea saccharalis e impactos na qualidade tecnológica e econômica da cana-de-açúcar - Belém, Camila de Souza Queiroz Pinheiro de (2017)
The sugarcane borer, Diatraea saccharalis (F.) (Lepidoptera: Crambidae), is an important pest of sugarcane (Saccharum spp.). Galleries are produced within the stalks as a result of the larval feeding. The holes allow the entry of microorganisms and fungi that can modify the technological quality of the raw material that goes to the industry. In this context, the objective was to estimate the influence of infestation intensity of D. saccharalis on the sugarcane technological quality and economic in different varieties. Two experiments were carried out. One with plants collected in September 2014 and another with plants collected in July 2015. In both of them was used completely randomized design with five repetitions. Treatments resulted of a factorial combination between three sugarcane varieties (IAC91-1099, RB86 7515 e CTC 4) and six infestation intensities of D. saccharalis (0%, 20%, 40%, 60%, 80% e 100%). Each plot corresponded to cane internodes with percent internodes with borer and rot corresponding to infestation intensities. The contents of Brix in the juice, Pol in the juice, fiber of the cane, Pol in cane, Purity of the juice, juice reducing sugars, stalk reducing sugar and total recoverable sugar were evaluated. The influence of the infestation intensity of D. saccharalis on sugarcane varies between the varieties and between the harvesting seasons. The presence of red rot in sugarcane does not necessarily imply loss of technological quality. The level of control should not be generalized and should be established taking into account varieties and harvesting carried out in the middle and at the end of the harvest.